2002
DOI: 10.1034/j.1600-0560.2002.290902.x
|View full text |Cite
|
Sign up to set email alerts
|

p63 expression in normal skin and usual cutaneous carcinomas

Abstract: Background:  p63 is a p53 homologue that is mapped to chromosome 3q27. This gene encodes six different isoforms, which have either transactivating or dominant negative effects on p53‐reporter genes. It has been described that in contrast to p53, p63 seems not to be associated with tumor predisposition, as neither p63 knockout mouse models nor germline p63 mutations are related to an increased risk of tumorigenesis. It has been demonstrated that p63 is a reliable keratinocyte stem cell marker and that it is inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

31
145
1
5

Year Published

2003
2003
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 142 publications
(182 citation statements)
references
References 21 publications
31
145
1
5
Order By: Relevance
“…p63 clearly plays a critical role in epidermal development and homeostasis both in mice and humans (15)(16)(17), but it is still unclear if p63 plays a role in carcinogenesis. While p63 has been reported to be absent or reduced in some human cancers, including basal cell carcinomas (18), it has more frequently been reported to be overexpressed in various tumors (19,20), including non-melanoma skin cancers (21)(22)(23)(24). Similarly, conflicting data from mice heterozygous for p63 have not resolved whether p63 is a tumor suppressor or oncogene (25)(26)(27).…”
Section: Introductionmentioning
confidence: 88%
“…p63 clearly plays a critical role in epidermal development and homeostasis both in mice and humans (15)(16)(17), but it is still unclear if p63 plays a role in carcinogenesis. While p63 has been reported to be absent or reduced in some human cancers, including basal cell carcinomas (18), it has more frequently been reported to be overexpressed in various tumors (19,20), including non-melanoma skin cancers (21)(22)(23)(24). Similarly, conflicting data from mice heterozygous for p63 have not resolved whether p63 is a tumor suppressor or oncogene (25)(26)(27).…”
Section: Introductionmentioning
confidence: 88%
“…Kaufmann et al The expression of p63 in normal human epidermis, cutaneous appendages and skin carcinomas has been recently assessed. [16][17][18] p63 seems to play a major role in ectodermal development, in the maintenance of the basal cell population of stratified epithelia, and also in the terminal differentiation of epithelia. [6][7][8] In vitro studies, using transformed human keratinocytes, have shown that p63 is a nuclear transcription factor that triggers keratinocyte differentiation and is downregulated in terminally differentiated cells.…”
Section: Discussionmentioning
confidence: 99%
“…10,12,14 The expression of p63 in normal human epidermis, cutaneous appendages and skin carcinomas has been recently assessed. 16,17 In these studies, p63 was detected in the epidermal and adnexal basal/ myoepithelial cells and it has been suggested that p63 might be used as a diagnostic marker for epidermal or adnexal tumors in the skin. [16][17][18] Cutaneous metastases may be the initial manifestation of some neoplasms, including adenocarcinomas.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[2][3][4] It has been advanced that p63 plays a role in triggering the differentiation of some specific cell lineages. [2][3][4][5][6][7] We have previously shown that p63 and basal keratins are restricted to the main cells, being negative in the C cells and in other thyroid structures, and advanced that the main cells of the solid cell nests display a basal/stem cell phenotype. 8 Bcl-2 overexpression has also been associated with stem cells.…”
mentioning
confidence: 99%